Intervensi Edukasi Berbasis Self-Care Untuk Pencegahan Masalah Kesehatan Mental Pada Remaja - Gusni Rahma; Yulia; Welly; Febry Handiny (Jurnal Pengabdian Ilmu Kesehatan (JPIK), 2025)
Adolescent mental health problems have become an increasingly significant public health concern. The 2018 National Basic Health Survey (Riskesdas) reported a 6% prevalence of emotional mental disorders among individuals aged ?15 years. Prior research conducted in the Belimbing Primary Health Care area found that 43.9% of adolescents experienced poor mental health, with a history of bullying identified as the dominant contributing factor (PR = 2.84). This activity aimed to enhance adolescents’ knowledge and attitudes regarding self-care as a preventive strategy against mental health problems. The educational intervention was delivered through video presentations and interactive discussions covering mental health concepts, early signs of stress and mental health disorders, and practical skills for implementing self-care in daily life. Evaluation of the program was conducted using a pre–post test questionnaire. The results indicated an increase in good knowledge from 45% to 85% and an improvement in positive attitudes from 50% to 90%. These findings demonstrate that the intervention was effective in improving adolescents’ understanding of the importance of self-care.